Integrating al-qur’an, hadith, and science in islamic education: Tracing scientific insights - Ihah Solihah; Isma Hisbullah Aljauhany; Khaibar Akmaluddin; Ahmad Mustafidin; Safa Alrumayh; Alfian Eko Rochmawan; Abdul Azid (Yayasan Azhar Amanaa Yogyakarta, 2025)
Islam views knowledge as a fundamental element of human life, emphasizing the harmonization between revelation and reason in the pursuit of truth. The Qur’an and Hadith serve as the primary sources of moral and transcendental values, while reason and science function as instruments to understand the phenomena of Allah’s creation. Thus, in Islam, knowledge is not solely directed toward material advancement, but also serves as a means of spiritual devotion and the welfare of the community. This study employs a library research method to examine the concept of knowledge in Islam and its relevance to the development of modern science. The findings reveal that Islam not only encourages scientific exploration but also provides an ethical foundation for its application. In fields such as cosmology, astronomy, embryology, and modern technology, numerous scientific discoveries affirm the Qur’anic indications of the orderliness of Allah’s creation. This demonstrates that science and religion in the Islamic perspective are not opposing entities, but rather complementary ones. Although debates persist on certain issues, such as the theory of evolution or the concept of the multiverse, these discourses are not threats to Islamic teachings. Instead, they open space for contemporary ijtihad that enriches the body of Muslim scholarship. By positioning revelation as a moral compass and science as a technical instrument, Islam offers a balanced scientific paradigm—one that avoids the traps of secular scientism that neglects spirituality, as well as textual literalism that denies rationality. Accordingly, this study affirms that the integration between Islam and science is a path toward building an advanced, sustainable civilization rooted in divine values. Science becomes a means of tafakkur that deepens faith, while revelation provides ethical direction and spiritual purpose in the utilization of knowledge. The synergy between the two is crucial for the development of Islamic education, enabling the emergence of generations who are intellectually excellent while remaining spiritually and morally steadfast.